ANALYSIS OF FACTORS AFFECTING INCOME OF THE JATILUWIH PENEBEL TOURISM OBJECT, TABANAN DISTRICT - Nita Manika Sari; Ida Bagus Wiratmaja; Ngurah Wisnu Murthi (Jurnal Ilmiah Satyagraha, 2024)
Tourism is one sector that makes an important contribution to national and regional economic growth. The Province of Bali is one of the areas that has become the highest tourist destination in Indonesia, in fact the Province of Bali was awarded as the best tourist destination (Island Destination of The Year) from the 2013 China Travel and Meeting Industry Award. This study uses a quantitative approach and analysis method, namely research in the form of numbers and statistical analysis with the aim of testing the hypotheses that have been set. Multiple linear regression method, partial test and F test simultaneously. Result 1 was obtained based on the SPSS calculation findings. The number of visitors, ticket pricing, and working hours all have a positive and considerable impact on income at the Jatiluwih Tourism Object in the Penebel District of Tabanan Regency. 2). According to the findings of the study, the number of visitors, ticket rates, and operating hours all have a major impact on income at the Jatiluwih Tourism Object in Penebel District, Tabanan Regency.